Hypoxia and hypoxia-inducible factor signals regulate the development, metabolism, and function of B cells - Zhang, Jinwei; Wu, Xiaoqian; Ma, Jideng; Long, Keren; Sun, Jing; Li, Mingzhou; Ge, Liangpeng (Frontiers in Immunology, 2022)
Hypoxia is a common hallmark of healthy tissues in physiological states or chronically inflamed tissues in pathological states. Mammalian cells sense and adapt to hypoxia mainly through hypoxia-inducible factor (HIF) signaling. Many studies have shown that hypoxia and HIF signaling play an important regulatory role in development and function of innate immune cells and T cells, but their role in B cell biology is still controversial. B cells experience a complex life cycle (including hematopoietic stem cells, pro-B cells, pre-B cells, immature B cells, mature naïve B cells, activated B cells, plasma cells, and memory B cells), and the partial pressure of oxygen (PO2) in the corresponding developmental niche of stage-specific B cells is highly dynamic, which suggests that hypoxia and HIF signaling may play an indispensable role in B cell biology. Based on the fact that hypoxia niches exist in the B cell life cycle, this review focuses on recent discoveries about how hypoxia and HIF signaling regulate the development, metabolism, and function of B cells, to facilitate a deep understanding of the role of hypoxia in B cell-mediated adaptive immunity and to provide novel strategies for vaccine adjuvant research and the treatment of immunity-related or infectious diseases.